PENGARUH MEDIA SOSIAL INSTAGRAM TERHADAP PERILAKU KEAGAMAAN REMAJA (STUDI PADA LINGKUNGAN IX DESA SINAKSAK KECAMATAN TAPIAN DOLOK KABUPATEN SIMALUNGUN) - Fazrul Falah; Muhammad Al Fikri; Fakhrur Rozi (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study aims to determine the extent of the influence of Instagram social media on adolescent religious behavior in terms of morals and religious behavior based on Islamic teachings. This research is a quantitative study using observation data collection methods and questionnaire distribution through google form. The data analysis method used in this research is the data validity and reliability test. Then processing the data using the SPSS application. The population in this study was 412 teenagers in Neighborhood IX Tapian Dolok District, Simalungun Regency. With the conditions that researchers must require as respondents in this study. Respondents in this study must be teenagers who follow Hanan Attaki's Instagram account so that a sample of 80 respondents can be determined in this study. Through the Uses and Effect theory that researchers do that there is an influence of Instagram social media on the influence of Instagram social media on an average percentage of 45.0% and most experience changes in religious behavior after seeing Hanan Attaki's content. So, it can be concluded that Instagram social media can change the religious behavior of adolescents.